Student-Initiated Interprofessional Case Discussions: Improving Students’ Perception of Interprofessional Education and Collaborative Practice / Studierenden-initiierte Interprofessionelle Fallbesprechungen: Verbesserung der studentischen Wahrnehmung von interprofessioneller Ausbildung und Zusammenarbeit - Büsser Lucas; Mulder Fanny; Zweifel Corina; Huber Marion (International Journal of Health Professions)
Opportunities for interprofessional education (IPE) remain insufficient for healthcare students and young professionals. To address this, the Swiss Health Alliance for Interprofessional Education (SHAPED, www.shaped-ip.ch) has developed a new IPE activity: the Interprofessional Case Discussions (ICDs). Led by a near-peer facilitator, students from different healthcare professions discuss a clinical case in a “murder-mystery” format: Can they catch the murderer (aka the disease) in time to save the patient? This study assessed the impact of the student-initiated ICDs on participants’ IPE perception.